ESTIMATING THE VALUE OF URBAN GREEN SPACE: A HEDONIC PRICING ANALYSIS OF THE HOUSING MARKET IN COLOGNE, GERMANY - Kolbe, Jens; Wüstemann, Henry (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
Urban Green Spaces (UGS), such as parks and forests, provide a wide range of environmental and recreational benefits. One objective in the conservation efforts of UGS is to analyse the benefits associated with UGS in order to make them more visible and to provide support for landscape planning. This paper examines the effects of UGS on house prices applying a Hedonic Pricing Method (HPM). The data set contains over 85046 geo-coded apartment transactions for the years 1995-2012 and contains information on three intrinsic variables of the real estate (e.g. transaction price, floor area and age). In order to examine the capitalisation of UGS in real estate prices, we further incorporated cross-section geo-coded data for the different types of UGS: forests, parks, farmland and fallow land drawn from the European Urban Atlas (EUA) of the European Environment Agency for the year 2006. In order to control for additional open space categories, we further incorporated geo-coded data on water bodies and fallow land. Using a Geographical Information System (GIS), we calculated the coverage of UGS in pre-defined buffers around households as well as the distance in a continuous fashion (Euclidian distance) between UGS and the households. Our results show a capitalisation of UGS in real estate prices, but the effect of the structural variables is higher. We found a positive price effect of parks, forests and water and an inverse relation between the price variable and the presence of fallow land and farmland.